Learning styles, study habits and academic performance of university students - Pajuelo Garay, Paola Elizabeth (2019)
Objective. To determine the relationship among learning styles, study habits and academic performance of university students. Methods. The study was descriptive, with quantitative approach and correlational design. The sample was 108 students selected by a non- probabilistic sampling. Instruments used were the Index of Learning Styles of Felder and Silverman and the questionnaire of Study Habits and Motivation for Learning (SHML). Results.They showed a visual learning style (76.9%), followed by sequential style (70.4%), active style (66.7%) and verbal style (23.1%). In addition, students that showed a good level of study habits were 54.6% (59), followed by 38.9% (42) at a very good level, and a lower number of students (6 and 1) were placed in regular and excellent levels, respectively. The average academic performance of the students distributed was: in a bad level 38.9%, in a regular level 50.9%, and at a good level 10.2% Conclusion. There is a positive relationship between learning styles and academic performance. There is also a positive relationship between study habits and academic performance. A positive correlation was determined between learning styles and academic performance variables, with a recording of Pearson correlation coefficient of 0.3 and a p <= 0.002. It was equally positive in the case of the correlation between study habits variables of and academic performance, where a Pearson correlation coefficient of 0.3 and a p <= 0.005 was obtained.